Une double conduite en bois découverte avenue du Point-du-Jour à Lyon - Sylvain Motte (Gallia)
An excavation conducted at 73-75-77 avenue du Point-du-Jour in Lyon (Rhône) in January 2020 brought to light a hydraulic system consisting of a double wooden pipe.The two parallel pipes lie in a ditch measuring 4 m in width and 2.80 m in depth. On the site, the work extends for a cumulative length of 24 m.The two assemblies consist of large-diameter segments of oak trunks (Quercus sp.) that could feed numerous developments. Radiocarbon and dendrochronological analyses as well as coins date this aqueduct precisely to the beginning of the 1st century AD.This accurate date and the location of the structure suggest a connection with the Yzeron aqueduct. It might have been a provisional route or a diversion caused by work on the main channel. It is also possible that the structure was independent of the Yzeron aqueduct.Also discovered on this site was one pier of the Roman Brévenne aqueduct. The base of this massive cubic section of masonry (2.70×2.64 m) stood in the ditch itself, destroying the original twin wooden pipe.